(untitled) (Third Sector Social Economic Review, 2018)
Understanding the World and behaviors require to known the history of economic thoughts and ideas for changing the World where new ideas may produce. On the time journey of the economy household management, shaping of society, needs, and sustainability of life specify the wealth of nations. Economic context described microeconomic; resources-production-sharing-distribution-consumption-recycling-and resources again, and macroeconomic; monetary, national income, employment, and growth. Some thoughts of economics such as mercantilism, physioracy, liberalism have been managing democratic and republic governments. Even though pessimistic and optimistic approaches, mainly pessimistic population theory explain rare resources cannot need highlighted about utilitarian ideas, support of utilitarian ideas to social welfare, and morality. When comparative advantages proposing specification of nation on the best activities, rant and increasing rant, opportunities cost, ownership of some people for everything, value of human, and labor value theory have been the current every time. Innovation, technology, creative destruction, alternative business cycles, human behaviors in the artificial cycles, human actions, legal and economic mergers, collaborations, democracy, social change, government supports, money supply, central bank, scientific ideas, the balance of social preferences of families and economic thoughts have been popular economy contents. Finally, value for everyone, choosing managers with respect of labor value, assets funding and participation partnership have been important in the process of business, income, saving, and investment as revival of society.